Numerical Analysis on Reinforcement Range of a Closed Steel Sleeve against Collapse - Qing-Feng Yin (Advances in Civil Engineering)
Before the shield machine begins to excavate, the end of the station structure often requires extensive soil reinforcement to ensure construction safety. Closed steel sleeve can prevent water leakage, sand leakage, and cave door collapse by balancing the water and soil pressure on the tunnel surface, thereby reducing the reinforcement range. In this study, a launching project of a closed steel sleeve is investigated; the Madis GTS finite element analysis software is used to simulate the triple-tube high-pressure jet-grouting pile to reinforce the water-rich sand layer. Soil displacement and stress after opening of the tunnel door are studied in detail at different longitudinal reinforcement lengths and transverse reinforcement scopes. The results show that, as the longitudinal reinforcement length increases, the displacement of the soil shows a decreasing trend, and the greater the length of the reinforced soil, the smaller the reduction in displacement. Furthermore, with the decrease of the lateral reinforcement range, though the soil settlement area has increased, the displacement remains unchanged. However, changing the end reinforcement range has no effect on the soil stress. In general, based on the strength and stability of the soil after the gate is cut out, the reinforcement range of the closed steel sleeve can be appropriately reduced compared to traditional reinforcement methods.